Purification, structural characterization and immunological activity of Sibiraea laexigata (L.) Maxim polysaccharide - Yang, Xuhua; Liu, Honghai; Yang, Jutian; Ma, Zhongren; Guo, Penghui; Chen, Hong; Gao, Dandan (Frontiers in Nutrition, 2022)
Sibiraea laexigata (L.) Maxim (SLM) has been used as an herbal tea for treating stomach discomfort and indigestion for a long time in china. Polysaccharides have been identified as one of the major bioactive compounds in the SLM. In the present paper, ultrasonic-assisted enzymatic extraction (UAEE) method was employed in polysaccharides extraction derived from SLM using polyethylene glycol (PEG) as extraction solvent, two SLM polysaccharides (SLMPs) fractions (SLMPs-1-1 and SLMPs-2-1) were purified by DEAE Cellulose-52 and Sephadex G-100 chromatography in sequence. Then, the preliminarily structure of the two factions were characterized by chemical composition analysis, molecular weight measurement, UVS, HPLC-PMP, FT-IR, nuclear magnetic resonance (NMR) spectra analysis and SEM. The results showed that SLMPs-1-1 and SLMPs-2-1 with different molecular weights of 1.03 and 1.02 kDa, mainly composed of glucose (46.76 and 46.79%), respectively. The results of structural characterization from FT-IR, 1H NMR, and SEM revealed that SLMPs-1-1 and SLMPs-2-1 contained the typical pyranoid polysaccharide with α-glycosidic bond and β-glycosidic bond. Furthermore, it was found that SLMPs-1-1 could increase the levels of tumor necrosis factor-α (TNF-α) and interleukin-2 (IL-2), and alleviated the immune organs tissue damage of cyclophosphamide (Cy)-treated mice. RT-qPCR and Western-Blot analysis showed that SLMPs-1-1 could significantly up-regulated the levels of NF-κB, TLR4, which revealed that SLMPs-1-1 could participate in immunosuppressive protection of Cy-treated mice. These findings suggested that the potential of SLMPs-1-1 as an alternative immunostimulator could be used in food and pharmaceutical industries.